National Immunization Campaigns with Oral Polio Vaccine Reduce All-Cause Mortality: A Natural Experiment within Seven Randomized Trials - Andersen, Andreas; Fisker, Ane Baerent; Rodrigues, Amabelia; Martins, Cesario; Ravn, Henrik; Lund, Najaaraq; Biering-Sørensen, Sofie; Benn, Christine Stabell; Aaby, Peter (Frontiers in Public Health, 2018)
Background A recent WHO review concluded that live BCG and measles vaccine (MV) may have beneficial non-specific effects (NSEs) reducing mortality from non-targeted diseases. NSEs of oral polio vaccine (OPV) were not examined. If OPV vaccination campaigns reduce the mortality rate, it would suggest beneficial NSEs. Setting Between 2002 and 2014, Guinea-Bissau had 15 general OPV campaigns and other campaigns with OPV plus vitamin A supplementation (VAS), VAS-only, MV, and H1N1 vaccine. In this period, we conducted seven randomized controlled trials (RCTs) with mortality as main outcome. Methods Within these RCTs, we assessed whether the mortality rate was lower after-campaign than before-campaign. We used Cox models with age as underlying time and further adjusted for low birth-weight, season and time trend in mortality. We calculated the adjusted mortality rate ratio (MRR) for after-campaign vs before-campaign. Results The mortality rate was lower after OPV-only campaigns than before, the MRR being 0.81 (95% CI = 0.68–0.95). With each additional dose of campaign-OPV the mortality rate declined further (MRR = 0.87 (95% CI: 0.79–0.96) per dose) (test for trend, p = 0.005). No other type of campaign had similar beneficial effects. Depending on initial age and with follow-up to 3 years of age, the number needed to treat with campaign-OPV-only to save one life was between 68 and 230 children. Conclusion Bissau had no case of polio infection so the results suggest that campaign-OPV has beneficial NSEs. Discontinuation of OPV-campaigns in low-income countries may affect general child mortality levels negatively.